Factors Related to Functional Status among Patients with Ischemic Stroke - Pham Thi Nga (2019)
Purpose: To examine the relationships between age, co-morbidity, stroke severity, and functional status among patients with ischemic stroke. Design: Descriptive correlational design. Methods: The sample was 115 patients with ischemic stroke who were treated at the Thai Binh General Hospital, Vietnam. Data were collected from the patients’ hospital records and interviewed with 3 research instruments: 1) the National Institute of Health Stroke Scale (NIHSS), 2) Co-morbidity index, and 3) the Modified Barthel Activities of Daily Living Index. Spearman’s rho was employed to test the relationship among studied variables. Main findings: The results supported the proposed hypothesis that age, co-morbidity, and stroke severity were negatively related to functional status after two weeks of treatment (rs = - .42, rs = - .35, rs = - .90, p < . 05, respectively).